ELM and inter-ELM tungsten erosion sources in high-power, JET ITER-like wall H-mode plasmas - H.A. Kumpulainen; M. Groth; S. Brezinsek; G. Corrigan; L. Frassinetti; D. Harting; F. Koechl; J. Karhunen; A.G. Meigs; M. O'Mullane; J. Romazanov (Nuclear Materials and Energy, 2022)
Simulations of JET ITER-like wall high-confinement mode plasmas, including type-I edge-localised modes (ELMs), using JINTRAC for the background plasmas and ERO2.0 for tungsten erosion and transport, predict virtually perfect screening of the primary W erosion sources at the divertor targets during both the ELM and inter-ELM phases. The largest source of W influx to the main plasma is predicted to be the outer vertical divertor due to sputtering by energetic fuel (D, T) atoms from charge-exchange reactions. ERO2.0 predictions accurately reproduce the measured W I emission in the low-field side divertor, but underpredict the W II emission by a factor of 10. Potential reasons for the W II discrepancy include uncertainties in the atomic data, assumptions on the sheath properties and the sputtering angle distribution, and the impact of metastable states.